Analisis Sosial Terhadap Dinamika Solidaritas Masyarakat Desa Menjelang Hari Kemerdekaan Indonesia - Deko Anwarul Mustofa, Wiqno (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Abstract— Indonesia as an independent country, free from the shackles of colonialism, makes this the momentum of Indonesia's independence day. Every year Indonesian people celebrate independence by holding competitions as a tradition to commemorate the services of the heroes. In this momentum, community solidarity becomes stronger, working with each other indirectly, which is different from normal days. This research aims to answer the basis of their solidarity, with social analysis. This research uses a qualitative descriptive approach by exploring data through books, articles, journals and the internet.